Design of Waste Treatment Applications at PT. Rifansi Dwi Putra Using Visual Basic.Net and MySQL Database - Miftahul Jannah; Jenny Rosalina; Erliza Yubarda (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
PT. Rifansi Dwi Putra is a company that operates in the Oil and Gas Industry, especially in the Waste Handling Transportation (WHT) Project regarding Waste Transportation. PT. Rifansi Dwi Putra especially at the Sand Management Facility (SMF) in processing waste volume data already uses a computer and is supported by Microsoft Excel software. However, doing data input, searching, processing, and reporting takes a relatively long time. So that the resulting information is less accurate, thus requests for fast and accurate information are often late in presenting their reports. In this regard, to facilitate the process of data accuracy, it is better to create an application for data collection of waste volumes using Visual Basic Programming Language and MySQL database. To facilitate the operations department, especially in recording the volume of waste transported to the Sand Management Facility (SMF) and making reports on the volume of waste to control, repair, and process data based on information technology and help the obstacles faced. To produce applications in waste volume data collection to facilitate structured data input in the data entry process, make it easier to search waste volume data, and help the management team produce accurate waste volume reports, making it easier to make decisions. The user of this application is only owned by one person because it is still a single user or stand alone (desktop-based) and this application produces three reports, namely reports per day, reports per month and reports per unit.